2017
DOI: 10.1042/cs20160727
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cerebral hypoperfusion: a key mechanism leading to vascular cognitive impairment and dementia. Closing the translational gap between rodent models and human vascular cognitive impairment and dementia

Abstract: Increasing evidence suggests that vascular risk factors contribute to neurodegeneration, cognitive impairment and dementia. While there is considerable overlap between features of vascular cognitive impairment and dementia (VCID) and Alzheimer's disease (AD), it appears that cerebral hypoperfusion is the common underlying pathophysiological mechanism which is a major contributor to cognitive decline and degenerative processes leading to dementia. Sustained cerebral hypoperfusion is suggested to be the cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
239
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 284 publications
(251 citation statements)
references
References 148 publications
1
239
1
10
Order By: Relevance
“…Our preliminary ASL data also showed that prolonged reduction of CBF in BCAS model was sustained over longer period of 16 weeks. Furthermore, oxygen deficit and debt using oximetry in the BCAS model has already been robustly established as we recently detailed . Therefore, we suggest that long‐term BCAS mouse model in the current study induces prolonged reproducible chronic cerebral hypoperfusion similarly to that seen in AD patients, and this support our findings that key molecules in brain EVs of both BCAS mouse model and early AD subjects are induced by chronic cerebral hypoperfusion.…”
Section: Discussionsupporting
confidence: 88%
“…Our preliminary ASL data also showed that prolonged reduction of CBF in BCAS model was sustained over longer period of 16 weeks. Furthermore, oxygen deficit and debt using oximetry in the BCAS model has already been robustly established as we recently detailed . Therefore, we suggest that long‐term BCAS mouse model in the current study induces prolonged reproducible chronic cerebral hypoperfusion similarly to that seen in AD patients, and this support our findings that key molecules in brain EVs of both BCAS mouse model and early AD subjects are induced by chronic cerebral hypoperfusion.…”
Section: Discussionsupporting
confidence: 88%
“…Several animal models have been developed to gain mechanistic insights into the pathophysiology of the WM matter and enable translation to the clinic (Duncombe et al . ). While efficient models to examine the sequelae of global and focal ischaemic injury have been useful, they have been limited to explore fully the various features of WM changes in the context of cerebral hypoperfusion and cerebral SVD.…”
Section: Contribution Of Laboratory Animal Studiesmentioning
confidence: 97%
“…6 Vascular and cognitive dysfunction could be associated with reduced cerebral perfusion. 28 Therefore, we examined cerebral perfusion in the WKY-Trpv4 em4Mcwi rats using MRI with continuous arterial spin labeling. Our data show that the TRPV4-deficient rats have reduced cerebral perfusion.…”
Section: Trpv4 Channel Deletion Increases the Mrna Expression Of Mamentioning
confidence: 99%